Model Sosialisasi dan Edukasi Kearifan Lokal Pasar Sarwono sebagai Laboratorium IPS Mahasiswa - Wafiq Maulana Ibrahim; Saila Mizab Rifdal Kafili; Muhammad Fani Chakim; Agung Supriyanto; Noor Fatmawati (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
This This community service activity aims to optimize the utilization of local wisdom at Pasar Sarwono in Wonosoco Village, Kudus, as a Social Studies (IPS) learning laboratory for university students through socialization and educational programs. The method used is a community service approach with descriptive qualitative techniques, including Focus Group Discussions (FGD), literature review, and field observations. The results show that Pasar Sarwono holds great potential in strengthening contextual learning through direct practice, such as social interaction, a traditional economic system using wooden coins, the use of traditional Javanese clothing (lurik), and the preservation of local culture such as Wayang Klitik performances. Educational strategies were implemented through socialization with the community and village stakeholders, student field visits, and academic reflection. However, the program faced several challenges, including limited community awareness of the educational value of local culture, insufficient human resources among educators, and geographic and administrative constraints. These findings underscore the importance of integrating higher education with local communities to foster students’ social character and preserve cultural heritage. Ethnopedagogy and constructivism serve as the theoretical foundations in developing contextual and relevant Social Studies education in the era of globalization. It can be concluded that this traditional market functions not only as a center of economic activity but also as an educational space rich in local cultural values, such as the use of wooden coins, traditional lurik attire, and traditional culinary offerings.